(untitled) (International Journal of Medical and Surgical Sciences, 2015)
This study briefly reviews the main events and processes that lead to the formation of the nervous system in mammals. At the end of gastrulation, they begin a series of fundamental morphogenetic processes with the formation of the neural plate (start of neurulation) culminating in the attainment of a normal nervous system. Embryological ectodermal primordia involved in the formation of the nervous system are the neuroectoblast, the neural crest cells and placodes that will evolve based on inductive phenomena, mainly from the notochord, prechordal plate and ectoderm. During the embryonic period consolidates the final development plan of the nervous system: 1) it comes complete neural tube formation when closing the rostral and caudal neuropores, 2) the different placodes invaginate to help form the organs of senses and sensory ganglia of the head, 3) the neural crest cells migrate to give rise to sensory and autonomic constituents of the peripheral nervous system and 4) developing brain vesicles, which will derive all the constituents of the brain. In the fetal period nervous system increases its mass and ultimately strengthens their functional organization.